Global leadership for social justice taking it from the field to practice - Boske, Christa; Diem, Sarah (Advances in educational administration ;, 2012)
Global leadership for social justice : taking it from the field to practice proposes perspectives for conceptualizing the preparation of leaders for social justice and equity-oriented work in schools. Although faculty in the field of education have prepared thousands of school leaders, and the research continues to expand, limited research exists regarding how to prepare leaders for social justice work in schools, especially considering international contexts. This book builds on extant empirical and theoretical work in the area of educational leadership, and deepens understanding of what leading for social justice and equity-oriented work looks like within diverse schools.